The potential role of hsa_circ_0001079 in androgenetic alopecia via sponging hsa‐miR‐136‐5p. Issue 1 (17th November 2021) - Wei, Hanxiao; Xu, Xiaoyu; Yang, Shuai; Liu, Chang; Li, Qiang; Jin, Peisheng
Abstract: Background: Androgenetic alopecia (AGA) is an androgen‐dependent polygenic hereditary disease. Methods: Diseased hair follicles from 5 AGA patients and normal hair follicles from 5 healthy individuals were selected as specimens to carry out whole transcriptome sequencing. Multiple high‐expression circular RNAs (circRNAs) were screened from the diseased group. We further verified the presence of the circRNAs in the clinical specimens by real‐time fluorescence quantitative PCR (qRT‐PCR). Results: In total, 100 circRNAs were significantly upregulated, and 184 circRNAs were significantly downregulated. The top 10 upregulated circRNAs were hsa_circ_0101041, hsa_circ_0001578, hsa_circ_0135062, hsa_circ_0002980, hsa_circ_0005062, hsa_circ_0072688, hsa_circ_0133954, hsa_circ_0001079, hsa_circ_0005974, hsa_circ_0000489. The top 10 downregulated circRNAs were hsa_circ_0001278, hsa_circ_0031482, hsa_circ_0008285, hsa_circ_0003784, hsa_circ_0077096, hsa_circ_0001148, hsa_circ_0006886, hsa_circ_0000638, hsa_circ_0084521, and hsa_circ_0101074. Among top 10 upregulated circRNAs, hsa_circ_0001079 showed significantly high expression via large‐sample verification and clinical application potential. Based on a database comparison and base pairing analysis, we found that has‐miR‐136‐5p bound to hsa_circ_0001079 and that hsa‐miR‐136‐5p had potential binding sites with Wnt5A. Conclusion: In summary, through high‐throughput sequencing and bioinformatic analysis, a potential diagnostic marker for alopecia and a key circRNA that might adsorb microRNA (miRNA) through a sponging mechanism, thus mediating alopecia, were discovered in this study. Abstract : The relationship between hsa_circ_0001079 and AGA in this study suggests that hsa_circ_0001079 plays a key role in the occurrence and development of AGA. The reverse correlation and perfect binding sequence between hsa_circ_0001079 and miR‐136‐5p suggests that hsa_circ_0001079 might regulate Wnt5A mRNA to inhibit normal hair follicle growth through sponging adsorption of miR‐136‐5p and that Wnt5A also participates in multiple cellular DNA replication pathways. It is of great significance to study the expression profile of AGA circRNAs and determine novel biomarkers to provide new directions and strategies for the diagnosis and treatment of AGA.